2024
DOI: 10.1097/adm.0000000000001259
|View full text |Cite
|
Sign up to set email alerts
|

Responses to a “Typical” Morning Dose of Kratom in People Who Use Kratom Regularly: A Direct-Observation Study

Kirsten E. Smith,
Jeffrey M. Rogers,
Abhisheak Sharma
et al.

Abstract: Introduction Use of kratom has outpaced systematic study of its effects, with most studies reliant on retrospective self-report. Methods We aimed to assess acute effects following kratom use in adults who use regularly, and quantify alkaloids in the products, urine, and plasma. Between July and November 2022, 10 adults came to our clinic and orally self-administered their typical kratom dose; blinding procedures were not used. Physiological measures inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…One example is that kratom persists as a harm-reduction method to reduce opioid and other substance use ( 8 , 9 ). Previously, some consumers with opioid use disorder (OUD) history reported that kratom is not preferred over illicit opioids and do not report using kratom to achieve a euphoric “high” ( 10 , 11 ). More recently, among adults who use kratom regularly and prefer it to other substances, most do not use to become intoxicated or “high”, even among people with OUD history ( 12 ).…”
Section: Context Of Kratom Usementioning
confidence: 99%
See 1 more Smart Citation
“…One example is that kratom persists as a harm-reduction method to reduce opioid and other substance use ( 8 , 9 ). Previously, some consumers with opioid use disorder (OUD) history reported that kratom is not preferred over illicit opioids and do not report using kratom to achieve a euphoric “high” ( 10 , 11 ). More recently, among adults who use kratom regularly and prefer it to other substances, most do not use to become intoxicated or “high”, even among people with OUD history ( 12 ).…”
Section: Context Of Kratom Usementioning
confidence: 99%
“…Kratom is also used nonmedically to attenuate withdrawal symptoms from opioids, stimulants and alcohol ( 13 , 14 ). One survey found that a majority (94.8%) of kratom consumers had abstained from other substance use for at least 6 months, highlighting kratom’s role in nonmedically managing addiction ( 11 , 12 , 15 , 16 ).…”
Section: Context Of Kratom Usementioning
confidence: 99%
“…While kratom has only recently proliferated in the US, rural populations in Southeast Asia have historically used kratom as a remedy for common ailments, to ameliorate fatigue, and as an adjunct to social and religious events ( Singh et al, 2017 ). Reports of perceived benefits have not been tested in randomized trials but have been recently systematically documented, along with other effects, using intensive longitudinal assessment in consumers’ daily lives ( Smith et al, 2024a ) and laboratory-based direct-observation of the acute effects of consumers’ self-selected dose ( Smith et al, 2024b ).…”
Section: Introductionmentioning
confidence: 99%